Transient Stability Enhancement of the Power System with Wind Generation - Sujith Mohandas; Ashwani Kumar Chandel (Universitas Ahmad Dahlan, 2011)
Transient stability analysis of a power system with wind generation has been addressed in this paper. The effects of automatic voltage regulators, power system stabilizers, and static synchronous compensators on transient stability of a power system are investigated. Various simulation results show that addition of power system stabilizer and static synchronous compensators reduce the rotor angle oscillations. However, the static synchronous compensator shows better damping characteristics and improves the stability of the wind integrated system. It has been established that the static synchronous compensator damps out the speed oscillations in the shaft of the constant speed wind turbine. A transient impact index has been proposed to prove that the static compensator damps out the rotor oscillations.